Prospects of Services Trade Liberalization in Japan-RP Bilateral Agreement - Gloria O. Pasadilla (Philippine Institute for Development Studies (PIDS), 2004)
The paper provides a background for services trade negotiations with Japan. It summarizes various discussions on international trade in services, the challenge of further services trade liberalization, and the rise of regional trade agreements. It discusses the different modalities of services trade negotiations that have arisen out of the different regional and bilateral trading arrangements in different parts of the world. The paper also analyses the level of liberalization in services based on existing multilateral and regional commitments of the Philippines and Japan, and suggests a few key points in different services sector that can help the Philippines benefit more from a bilateral trade agreement with Japan.
Keywords: 330; regional trading arrangements; Japan-Philippines economic partnership; trade in services; General Agreement on Trade in Services (GATS); modes of services; Dienstleistungshandel; Freihandelszone; Philippinen; Japan